Analisis 7CFramework untuk Memprediksi Kinerja Pemasaran - Vincent Vincent; Dyah Budiastuti (The Winners, 2013)
One of the growing trends in recent decades that support the development of market share artwork is the mutation of a change in a means of artworks business. Market structure has changed along with the evolution of the Internet. Hall auction of artwork has implemented mobile auction as a form of Internet and mobile technology application. The purpose of this study is to identify the needs of mobile auction features suit to collectors of buyer and seller. The identification was based on the 7C framework on auction business process and PT Larasati Auctioneers’s marketing website. The survey was conducted on the collectors of buyer and seller; and analyzed using factor analysis. The final result describes the needs of mobile auction features and a prediction of marketing performance if mobile auction application is developped.